2013
DOI: 10.1128/iai.00515-13
|View full text |Cite|
|
Sign up to set email alerts
|

Adaptive Strategies and Pathogenesis of Clostridium difficile fromIn VivoTranscriptomics

Abstract: f Clostridium difficile is currently the major cause of nosocomial intestinal diseases associated with antibiotic therapy in adults. In order to improve our knowledge of C. difficile-host interactions, we analyzed the genome-wide temporal expression of C. difficile 630 genes during the first 38 h of mouse colonization to identify genes whose expression is modulated in vivo, suggesting that they may play a role in facilitating the colonization process. In the ceca of the C. difficile-monoassociated mice, 549 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

15
155
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 135 publications
(172 citation statements)
references
References 77 publications
15
155
2
Order By: Relevance
“…A few negative regulators of SigD have been identified, including the early sporulation effector RstA, the stationary-phase sigma factor SigH, and (24,39,48,49). We examined the transcription of rstA on sporulation medium and found that its expression was more than 3-fold lower in the CD1492 mutant than in the parent strain (Fig.…”
Section: Deletion Of Cd1492 Results In Decreased Virulence In An Animmentioning
confidence: 99%
“…A few negative regulators of SigD have been identified, including the early sporulation effector RstA, the stationary-phase sigma factor SigH, and (24,39,48,49). We examined the transcription of rstA on sporulation medium and found that its expression was more than 3-fold lower in the CD1492 mutant than in the parent strain (Fig.…”
Section: Deletion Of Cd1492 Results In Decreased Virulence In An Animmentioning
confidence: 99%
“…Lower nutrient uptake would cause derepression of CodY-and CcpA-responsive genes and increased SigD activity, all of which would result in higher toxin expression (53,56,63,72). A comparison of gene expression levels for C. difficile grown in vitro and in vivo found a substantially greater impact on metabolism and sporulation under in vivo conditions than under in vitro conditions (82). This discrepancy highlights the need for greater understanding of the nutritional environment present during C. difficile infections, which could be used to improve conditions for examining these physiological processes in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Once established in the gastrointestinal tract, C. difficile secretes two toxins, the enterotoxin TcdA and the cytotoxin TcdB, that cause massive damage to the intestinal epithelium and induce strong inflammatory responses (6). During growth in the gastrointestinal tract, C. difficile strongly induces a transcriptional program that leads to spore formation (7). Spore formation is essential for C. difficile to survive exit from the host and transmit disease because its vegetative cells are exquisitely sensitive to oxygen (8).…”
mentioning
confidence: 99%